ARAHAN PENGEMBANGAN PERMUKIMAN KECAMATAN BATANG ANAI DAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Kurnia Illahi; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
ABSTRACT The purpose of this research is to find out the suitability of residential land in Batang Anai and Lubuk Alung Districts and to determine the direction of settlement development in Batang Anai and Lubuk alung sub-districts. This research uses quantitative descriptive techniques using boolean logic. The results of this study indicate that not all of the land in Batang Anai and Lubuk Alung Districts is suitable for settlement. Based on the results of the analysis of land suitability with the parameters used, there are two categories of land namely suitable land and inappropriate land. Based on the results of the land suitability overlay, protected area and spatial plan of the cultivation area, the area that can be developed for settlements is 506 Ha and the land that is not suitable for development is 28322 Ha.